Evaluation of Diesel Engine Performance Using Biodiesel from Cooking Oil Waste (WCO) - Suardi, Suardi; Setiawan, Wira; Nugraha, Andi Mursid; Alamsyah, Alamsyah; Ikhwani, Rodlian Jamal (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2023)
The increasing use of fossil fuels will cause the world's oil reserves to be depleted. In this case, it is necessary to increase the use of alternative renewable fuels, one of which is biodiesel waste cooking oil (WCO). The method used is an experimental test with a mixture of used cooking oil biodiesel and fuel. Before testing, the temperature of each fuel is increased to determine the effect of temperature on the density and viscosity values. The highest density value is found in B50 fuel at 26 °C, with a density of 0.854 gr/ml, while the lowest density is found in diesel fuel at 60 °C, with a density of 0.822 gr/ml. The highest viscosity value is found in B50 fuel at 26 °C and 60 °C, which is 3.26 cSt. After that, testing was carried out on a diesel engine, which produced the highest thermal efficiency value of 21.16% on B50 fuel with a temperature of 60 °C at 1000 rpm rotation and a load of 4000 watts. The lowest thermal efficiency of 6.43% was found in B50 fuel with a temperature of 26 °C at 800 rpm and a load of 1000 watts. The lowest consumption was found in B30 with a temperature of 60 °C at 1200 rpm, which was 420.78 gr/kWh. From the results of the tests that have been carried out, it can be concluded that the lower the density and viscosity of the fuel, the better the performance of the diesel engine on average. High temperatures effectively make the engine performance value better than normal temperatures (26 °C), and the performance of diesel engines is better with WCO fuel, especially in SFC.